PENGARUH SOSIALISASI KESADARAN PAJAK, KETEGASAN SANKSI PAJAK, DAN PEMAHAMAN TARIF PAJAK PELAKU E-COMMERCE TERHADAP KINERJA PENERIMAAN PAJAK DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING: (STUDI KASUS DI KARESIDENAN SURAKARTA) - Nisrina Amaya; Indra Lila Kusuma; Rukmini Rukmini (CV. Denasya Smart Publisher, 2024)
This research aims to determine whether there is an influence of socialization of tax awareness, strictness of tax sanctions, and understanding of e-commerce tax rates on tax revenue performance through taxpayer compliance as an intervening variable. The population that is the object of this research is MSMEs who run their business through e-commerce in the Surakarta Residency, with a sample of 97 respondents. The data collection method in this research use a questionnaire with certain criteria (purposive sampling). The data analysis technique used to test direct and indirect effects uses path analysis with SPSS 26 software. The research results show that the socialization of tax awareness and the strictness of tax sanctions directly have a significant effect on taxpayer compliance, while understanding tax rates directly does not have a significant effect on taxpayer compliance. Then, socializing tax awareness and strictness of tax sanctions directly has a significant effect on tax revenue performance, but understanding tax rates directly does not have a significant effect on tax revenue performance. Taxpayer compliance is unable to mediate the influence of the relationship between socialization of tax awareness, strictness of tax sanctions, and understanding of tax rates on tax revenue performance in the Surakarta Residency